In-situ catalytic pyrolysis reaction of sugarcane bagasse over nickel-cerium/hzsm-5 for enhanced hydrocarbons in pyrolysis oil - Balasundram, Vekes (2018)
The catalytic of oxygenated pyrolysis vapour over HZSM-5 catalyst is of the preferred method to enhance the quality of pyrolysis oil. However, the content of C6 – C8 hydrocarbons in pyrolysis oil produced by this method is still low. Thus, the main aim of this study is to investigate the in-situ catalytic of oxygenated pyrolysis vapours from sugarcane bagasse into enhanced C6 – C8 hydrocarbons in pyrolysis oil over nickel-cerium/HZSM-5 catalyst. The first aim was to synthesize catalysts via incipient wetness impregnation and characterize via X-ray diffraction, field emission scanning electron microscopy-energy dispersive X-ray, Brunauer Emmett Teller, Fourier transform infrared, and temperature programmed desorption of ammonia. The HZSM-5 was fixed at 94 wt.%, while the balance 6 wt.% was impregnated at nickel to cerium mass ratios as follows: 1:5 (NC1), 2:4 (NC2), 3:3 (NC3), 4:2 (NC4), and 5:1 (NC5). The second aim was to investigate the performance of catalyst in the catalytic of oxygenated pyrolysis vapours into enhanced C6 – C8 hydrocarbons via in-situ fixed bed reactor at pyrolysis reaction temperature ranging from 400 – 600 °C. The catalyst to biomass mass ratios was as follows: 0.5:1.0 (CB1), 1.0:1.0 (CB2), 1.5:1.0 (CB3), 2.0:1.0 (CB4), 2.5:1.0 (CB5), and 3.0:1.0 (CB6). The results show that the in-situ catalytic of oxygenated pyrolysis vapours were significantly influenced by pyrolysis reaction temperatures, catalyst to biomass mass ratios, and nickel to cerium mass ratios. The highest total contents of C6 – C8 hydrocarbons in pyrolysis oil (8.82%) is attained at pyrolysis reaction temperature of 500 °C, catalyst to biomass mass ratio of 1:1, and nickel to cerium mass ratio of 3:3. The third aim was to optimize the process parameters via response surface methodology, in which the optimized C6 – C8 hydrocarbons in pyrolysis oil (8.90%) can be achieved at pyrolysis reaction temperature of 505 °C, catalyst to biomass mass ratio of 1.1:1.0, nickel to cerium mass ratio of 3.14:2.86. The final aim was to perform the kinetic analysis of catalytic pyrolysis process. For the kinetic analysis, the catalytic pyrolysis has achieved higher activation energy (34.02 – 122.23 kJ/mol) than the non-catalytic pyrolysis (17.17 – 66.90 kJ/mol) using the Flynn-Wall-Ozawa method. The reaction mechanisms of non-catalytic and catalytic pyrolysis obtained via the Coats-Redfern method follows power law (n = 1) and chemical reaction (n = 2) respectively. Finally, the catalytic of oxygenated pyrolysis vapours over nickel-cerium/HZSM-5 catalyst can produce high contents of hydrocarbon fuel directly from sugarcane bagasse.